2014
DOI: 10.1073/pnas.1404346111
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale topology and the default mode network in the mouse connectome

Abstract: Noninvasive functional imaging holds great promise for serving as a translational bridge between human and animal models of various neurological and psychiatric disorders. However, despite a depth of knowledge of the cellular and molecular underpinnings of atypical processes in mouse models, little is known about the large-scale functional architecture measured by functional brain imaging, limiting translation to human conditions. Here, we provide a robust processing pipeline to generate high-resolution, whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

42
280
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(323 citation statements)
references
References 58 publications
(74 reference statements)
42
280
1
Order By: Relevance
“…supplementary, barrel field, and visual, and areas proposed to contribute to the "rodent default-mode network" ("DMN"), namely prefrontal and cingulate cortices (Gozzi and Schwarz, 2016;Sforazzini et al, 2014;Stafford et al, 2014). The present findings were robust and reproducible, as evidenced by the similar and significant CPS effects on network strengths obtained in each run, comprising 12-15 mice per CPS and control group per run, and with similar variances observed in the CPS and control data sets.…”
Section: Increases In Within-and Between-network Functional Connectivsupporting
confidence: 78%
See 1 more Smart Citation
“…supplementary, barrel field, and visual, and areas proposed to contribute to the "rodent default-mode network" ("DMN"), namely prefrontal and cingulate cortices (Gozzi and Schwarz, 2016;Sforazzini et al, 2014;Stafford et al, 2014). The present findings were robust and reproducible, as evidenced by the similar and significant CPS effects on network strengths obtained in each run, comprising 12-15 mice per CPS and control group per run, and with similar variances observed in the CPS and control data sets.…”
Section: Increases In Within-and Between-network Functional Connectivsupporting
confidence: 78%
“…In rats, a recent rs-fMRI study demonstrated that the physical stressor of repeated immobilisation results in increased FC within the "DMN" as well as somatosensory-cortex and visual-cortex networks (Henckens et al, 2015). In mice, rs-fMRI has been applied to demonstrate that structurally connected brain areas also exhibit FC, that brain topology and networks exhibit homology with primate species (Stafford et al, 2014), and that network alterations are sensitive indicators of pathology (Grandjean et al, 2014b). In mice, chronic social stressors combined with behavioural tests have identified changes in emotional, motivational and cognitive states that are relevant to human psychopathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Because the DMN is an anatomically and functionally interconnected network (15), the fMRI activations in component areas tend to fluctuate in a coordinated manner even in anesthetized animals. However, some animal work has described a DMN based on awake-state data that is more in line with the studies in humans.…”
mentioning
confidence: 99%
“…30). As a starting point, our initial aim was to determine whether aged rats, like young animals (24,25,(31)(32)(33), display coherent rs-FC in the rodent homolog of the DMN, as defined by placing a seed in a key DMN hub, the retrosplenial/posterior cingulate cortex (RSC/PCC). Second, brain-wide rs-FC examined in this context allowed us to test whether changes in cortical network dynamics are specifically coupled with age-related cognitive decline or instead reflect an obligatory outcome of chronological aging.…”
mentioning
confidence: 99%